A cultural history of the avant-garde in the Nordic countries 1925-1950 - Hjartarson, Benedikt; Kollnitz, Andrea, 1970-; Stounbjerg, Per, 1956-; Ørum, Tania (Avant garde critical studies, 2019)
"A Cultural History of the Avant-Garde in the Nordic Countries 1925-1950 is the first publication to deal with the avant-garde in the Nordic countries in this period. The essays cover a wide range of avant-garde manifestations: literature, visual arts, theatre, architecture and design, film, radio, body culture and magazines. It is the first major historical work to consider the Nordic avant-garde in a transnational perspective that includes all the arts and to discuss the role of the avant-garde not only within the aesthetic field but in a broader cultural and political context: the pre-war and wartime responses to international developments, the new cultural institutions, sexual politics, the impact of refugees and the new start after the war."--Provided by publisher.